An amino-terminal domain of the Sendai virus nucleocapsid protein is required for template function in viral RNA synthesis. - Myers, T M (1997)
The nucleocapsid protein (NP) of Sendai virus encapsidates the genome RNA, forming a helical nucleocapsid which is the template for RNA synthesis by the viral RNA polymerase. The NP protein is thought to have both structural and functional roles, since it is an essential component of the NP0-P (P, phosphoprotein), NP-NP, nucleocapsid-polymerase, and RNA-NP complexes required during viral RNA replication. To identify domains in the NP protein, mutants were constructed by using clustered charge-to-alanine mutagenesis in a highly charged region from amino acids 107 to 129. Each of the mutants supported RNA encapsidation in vitro. The product nucleocapsids formed with three mutants, NP114, NP121, and NP126, however, did not serve as templates for further amplification in vivo, while NP107, NP108, and NP111 were nearly like wild-type NP in vivo. This template defect in the NP mutants from amino acids 114 to 129 was not due to a lack of NP0-P, NP-NP, or nucleocapsid-polymerase complex formation, since these interactions were normal in these mutants. We propose that amino acids 114 to 129 of the NP protein are required for the nucleocapsid to function as a template in viral genome replication.